(untitled) (Research, Society and Development, 2022)
Objective: To identify the sensitivity and specificity of Fine-Needle Aspiration Biopsies (FNAB) performed at Hospital Regional da Asa Norte (HRAN) for the diagnosis of thyroid cancer in patients submitted to thyroidectomy. Methods: This was an observational and analytical study, which analyzed medical records of patients submitted to FNAB at HRAN from April 2015 to December 2021. The data were descriptively analyzed using the SPSS 2.0 program, and using the ROC Curve, considering a p value <0.05 as statistically significant. Results: 699 patients were submitted to FNAB. 62 patients were undergoing biopsy and surgery after. FNAB sensitivity and specificity were 90.32% and 83.87%, respectively (p <0.001). Most patients were females (96.78%), aged > 60 years (32.25%) and were submitted to total thyroidectomy (66.12%). Among the analyzed cytopathological samples, the Bethesda II classification predominated (25.80%), followed by class V (22.58%). In the histopathological analysis, the predominant diagnosis was papillary carcinoma (43.54%) followed by goiter (38.70%). Among classes I and II, only one sample was considered malignant after the histopathological analysis. Among class III samples, 22.22% were, in fact, malignant lesions. Among the samples suspected of malignancy (Bethesda IV, V and VI), there was a progressive increase in the rate of cancer diagnosis, of 62.50%, 85.71% and 100%, respectively. The FNAB results showed an accuracy of 87.09%. Conclusions: The results of this study are compatible with the findings in the literature. Thus, FNAB remains the gold standard for the analysis of thyroid nodules until another more sensitive and specific method is described.